Tipologi dan Determinan Motivasi Belajar Mahasiswa Pendidikan Bahasa Arab di UIN Sultan Maulana Hasanuddin Banten - Ali Maksum; Rosidah Rosidah; Noor Anzali; Umihani Umihani (Edu Journal Innovation in Learning and Education, 2026)
This study aims to identify the typology of learning motivation and analyze the factors that influence the learning motivation of students in the Arabic Language Education Program at UIN Sultan Maulana Hasanuddin Banten. This study employs a mixed-methods approach with a sequential explanatory design, integrating quantitative and qualitative data to gain a comprehensive understanding of students’ learning motivation. In the quantitative phase, data were collected through a questionnaire distributed to students in the Arabic Language Education Program and analyzed using descriptive and inferential statistics. Next, the qualitative phase was conducted through in-depth interviews with selected informants to confirm and enrich the quantitative findings. The results of the study indicate that students’ learning motivation can be classified into several typologies, namely intrinsic motivation, extrinsic motivation, and motivation oriented toward academic and professional achievement. The factors that influence learning motivation include interest in the Arabic language, family support, the academic environment, faculty competence, career prospects, and students’ learning experiences. The integration of quantitative and qualitative findings shows that intrinsic motivation is the dominant factor in driving student engagement in the learning process, although external factors also make a significant contribution. This study has implications for the development of learning strategies and academic policies aimed at strengthening students’ learning motivation in Islamic higher education settings.